Interactive HTML A byte size introduction - Fickas, Stephen (Prentice Hall, 1998)
Appropriate for courses on HTML and Web Programming as well as a supplemental text for Internet/WWW courses. This work is ideal for readers with limited time who would like to understand how to use HTML.